Analisis Permintaan Impor Indonesia: Pendekatan Komponen Pengeluaran - Agus Widarjono (Universitas Islam Indonesia, 2004)
This study analyzes Indonesian aggregate imports by using expenditure components approach since Indonesian Economy relies highly on import. The relationship between ag¬gregate imports and the component of final demand expenditure namely public and private consumption expenditure, investment expenditure and export is investigated because the dif¬ferent components of final demand expenditure have different import contents. In addition, the model also includes price of import as a determinant demand for import.Johansen Multivariate co integration is proposed to analyze the import behavior in the long run. To examine response of import to its determinants in the short run, an error correction model is applied. Quarterly data during 1990.1-2003.2 are used for the analysis. The results demonstrate both the components of final demand expenditure and price of im¬port are all important factor in determining aggregate demand for imports not only in the long run but also in the short run.Keywords: Demand for imports, Components of final demand expenditure, Cointegration, Error Correction Model.